Diseño multimedia informativo para dar a conocer las especies de aves en peligro de extinción de la Zona 3. - Jerez Faubla, Cristian Reinaldo (2019)
Digital communication such as video, web and apps to know about endangered bird species at Zone 3 in the National Parks and Ecological Reserves of Cotopaxi, Tungurahua, Chimborazo and Pastaza are scarce. Therefore, it was necessary to carry out an interactive multimedia product by using Card sorting techniques and User-Centered Design processes, to obtain as a result a functional prototype. The research techniques and analysis of illustrations, created as graphic editorial material collected content of the following birds: Andean condor, curiquingue, red macaw, quilico (Falco sparverius) and red bird. Technical information was also obtained from the processes and phases of the vector illustration so creative each feature and morphological characteristics of these species, which are ideal as digital content for having a realistic and detailed style. The themes that are included in the proposal of functional prototyping are; App starting icon, Primary navigation menu, birds, risks, glossary, gallery, camera, in the bird icon there is important information such as the scientific name of the species, vulnerability, feeding, geographical location and physical characteristics. This study was achieved through exploratory research, the qualitative one through interviews and the quantitative one through surveys. The methodology of the User-Centered Design proposed by Jakob Nielsen was used, which is based on the construction of a low-fidelity prototype through phases, establishing the creative process and the heuristic evaluation phases. The impacts of the project are: Environmental by generating resources that transmit digital information about the care of these species. Social: due to the research links the inhabitants of the sector as direct beneficiaries. Cultural: as an endorsement of the conservation and promotion of environmental diversity. Technological: because it is a useful research tool in the exemplification and application of methods for the construction of interactive multimedia products. As a final result of the research study, the functional prototype of the application constituted in a detailed prototyping of each bird, being a digital information tool where functional prototyping was the focus of the product, which attracted public attention.